SAFIRE STRENGTH OPTIMIZATION: EFFECT ON TISSUE CONTRAST AND PATHOLOGICAL ASSESSMENT OF BRAIN MSCT WITH NON-HEMORRHAGE STROKE (SNH) - Juliantara, I Putu Eka; Martoyo, Angel Lingkan; Pratista, Made Sayang (Faculty of Vocational Studies, Universitas Airlangga, 2024)
Background: Sinogram Affirmed Iterative Reconstruction (SAFIRE) is an Iterative Reconstruction algorithm that combines IR techniques that utilize raw data and image data iterations as parameters that underlie noise regularization in images in the reconstruction process to improve image quality. Purpose: Analyze the effect of variations in SAFIRE strength values on image contrast and pathological evaluation of CT scan brain with clinical Stroke Non-Hemorrhage (SNH). Method: This research is a quantitative analytic study with an experimental approach to analyze the effect of SAFIRE strength values on image contrast and pathological assessment on CT scan brain examination. Result: Statistical test results showed a significant difference (p-value < 0.05) in all variations of SAFIRE strength, with the resulting Contrast-to-Noise Ratio (CNR) value increasing as the SAFIRE strength value used increased. The average CNR improvement was 18.4% on all SAFIRE strength values compared. This increase is affected by a linear decrease of the noise value from one SAFIRE strength value to another. Image contrast improvement also affects the pathological assessment of SNH due to the increased density differences in the hypodense lesion compared to the surrounding tissues. Conclusion: The use of the SAFIRE strength variation significantly affects image contrast values and pathological assessment in the SNH brain MSCT examination.